S3 Electronic monitoring of adherence to inhaled corticosteroids in pre-school children with wheeze. (December 2018) - Bingham, Y; Sanghani, N; Cook, J; Hall, P; Jamalzadeh, A; Moore-Crouch, R; Fleming, L; Bush, A; Saglani, S
Abstract : Introduction: Adherence to inhaled corticosteroids (ICS) is known to be suboptimal in school-age children with difficult asthma (DA) (Jochmann ERJ 2017; 50(6)). Little is known about adherence to ICS in pre-school children with wheeze. We hypothesised that adherence to ICS and symptom control are positively related, independent of clinical phenotype, and that a period of adherence monitoring would increase symptom control in pre-school children with wheeze. Methods: Patients aged between 1 and 5 years with recurrent wheeze who had been prescribed maintenance inhaled corticosteroids were recruited from a tertiary paediatric respiratory clinic. Clinical phenotype was determined at recruitment, adherence was assessed using an electronic monitoring device (Smartinhaler) and Symptom control was assessed using the Test for Respiratory and Asthma Control in Kids (TRACK). Results: 21 children (median age 42 months, range 21–69 months) were monitored for a median of 16 (range 4–52) weeks. Clinical phenotypes at baseline were: episodic viral wheeze (EVW) n=15, multiple trigger wheeze (MTW) n=6. 14/21 (67%) wheezers had sub-optimal ICS adherence (<80%). Median adherence was 65% (Range (0–91). There was a significant increase in TRACK score between baseline and follow up visits (p=0.02), however, change in TRACK was not related to ICS adherence (figure 1). Conclusions: Adherence to ICS was lower in pre-school children with moderate to severe wheeze, than in school-age children with DA, and was unrelated to clinical phenotype. Symptom control improved following a period of monitoring in pre-school wheezers, but was unrelated to adherence. This suggests the improved symptoms may be related to the natural history of pre-school wheezing rather than treatment efficacy. Currently we need to better target ICS use in pre-school children.